1978
DOI: 10.1017/s0007485300009354
|View full text |Cite
|
Sign up to set email alerts
|

The use of ageing techniques to evaluate the effects of aerial spraying against Glossina morsitans centralis Machado (Diptera: Glossinidae) in northern Botswana

Abstract: During a large-scale air-spray trial using endosulfan against Glossina morsitans centralis Machado in the Okavango Delta area of Botswana, a programme of ageing all flies caught on fly-rounds was undertaken. The aim was to evaluate closely the effect of repeated sprays on the population and especially to determine the origin of the small residual population that often remains after spraying. Ageing males by the wing-fray method indicated that none survived the spraying. Ageing females toy ovarian dissection sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

1980
1980
2011
2011

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 11 publications
0
22
0
Order By: Relevance
“…For effective control/eradication, every female fly must receive a dose of insecticide sufficient to kill it and its in utero larva. Davies [1978] suggested that short time intervals between non-residual sprays would ensure that latepregnant flies surviving the first spray will be hit by the next spray early in their next pregnancy (and that the spray series should continue long enough to kill emergents from puparia formed at the time of the first spray).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For effective control/eradication, every female fly must receive a dose of insecticide sufficient to kill it and its in utero larva. Davies [1978] suggested that short time intervals between non-residual sprays would ensure that latepregnant flies surviving the first spray will be hit by the next spray early in their next pregnancy (and that the spray series should continue long enough to kill emergents from puparia formed at the time of the first spray).…”
Section: Discussionmentioning
confidence: 99%
“…Increased insecticide-tolerance by pregnant tsetse, compared with non-pregnant specimens, was shown for several species and insecticides [Burnett, 1962;Hadaway, 1972;Irving, 1968;Kwan et al, 1982] and Irving [1968] suggested that diversion of absorbed insecticide into in utero larvae protected pregnant flies from lethal action. Davies [1978] showed that all flies (Glossina morsitans centralis Machado) surviving endosulfan-spraying in Botswana were pregnant and mentioned the usefulness of knowing the fate of the progeny of these flies.…”
Section: Introductionmentioning
confidence: 99%
“…Pregnant tsetse have greatly raised tolerance t o topical applications of insecticide, because a large part of the dose is diverted t o the larva in utero (Irving, 1968). This is assumed to be the reason that the only tsetse flies that consistently survive non-residual, aerosol insecticide sprays in the field are pregnant females (Davies, 1978). Kwan e t al.…”
Section: Potential Insecticide Avoidancementioning
confidence: 99%
“…Finally, the lack of visual responsiveness before and around larviposition suggests that the contemporary inactivity (Brady & Gibson, 1983) and photonegativity (Rowcliffe & Finlayson, 1982) go hand-in-hand with a general unarousability, which is likely t o lead t o a strong tendency for pregnant females to stay put in dark shelters, and thus avoid exposure t o ULV insecticide applicationsa further reason for their unusual ability t o survive such sprays (Davies, 1978).…”
Section: Discussionmentioning
confidence: 99%
“…Not only d o they become almost totally immobile for some 4 8 h before depositing a larva, but their circadian rhythm is also much modified: 2 days before larviposition the morning peak of their typical V-shaped flight pattern is over twice as high as normal; virtually no activity occurs for the whole of the day preceding larviposition; and on the day of larviposition, whereas the morning peak of the V is still heavily suppressed, there then occurs a wholly untypical period of high activity in the early afternoon just preceding parturition. Brady & Gibson (1983) postulated that, by preventing heavily pregnant females from flying out into insecticide clouds, this 48 h of inactivity, associated with such females' concurrent photonegativity (Rowcliffe & Finlayson, 1982) might be one reason for the fact that pregnant females are the only members of G.morsitans populations t o survive aerosol non-residual insecticide campaigns (Davies, 1978). The other and perhaps principal reason is that any insecticide picked u p by pregnant females tends to be shunted to the larva via the female's highly lipid 'milk' (see Kwan et al, 1982).…”
Section: Introductionmentioning
confidence: 99%